Direct Actions of AT(1) (Type 1 Angiotensin) Receptors in Cardiomyocytes Do Not Contribute to Cardiac Hypertrophy - Sparks, Matthew A. (Hypertension, 2021)
Activation of AT(1) (type 1 Ang) receptors stimulates cardiomyocyte hypertrophy in vitro. Accordingly, it has been suggested that regression of cardiac hypertrophy associated with renin-Ang system blockade is due to inhibition of cellular actions of Ang II in the heart, above and beyond their effects to reduce pressure overload. We generated 2 distinct mouse lines with cell-specific deletion of AT(1A) receptors, from cardiomyocytes. In the first line (C-SMKO), elimination of AT(1A) receptors was achieved using a heterologous Cre recombinase transgene under control of the Sm22 promoter, which expresses in cells of smooth muscle lineage including cardiomyocytes and vascular smooth muscle cells of conduit but not resistance vessels. The second line (R-SMKO) utilized a Cre transgene knocked-in to the Sm22 locus, which drives expression in cardiac myocytes and vascular smooth muscle cells in both conduit and resistance arteries. Thus, although both groups lack AT(1) receptors in the cardiomyocytes, they are distinguished by presence (C-SMKO) or absence (R-SMKO) of peripheral vascular responses to Ang II. Similar to wild-types, chronic Ang II infusion caused hypertension and cardiac hypertrophy in C-SMKO mice, whereas both hypertension and cardiac hypertrophy were reduced in R-SMKOs. Thus, despite the absence of AT(1A) receptors in cardiomyocytes, C-SMKOs develop robust cardiac hypertrophy. By contrast, R-SMKOs developed identical levels of hypertrophy in response to pressure overload–induced by transverse aortic banding. Our findings suggest that direct activation of AT(1) receptors in cardiac myocytes has minimal influence on cardiac hypertrophy induced by renin-Ang system activation or pressure overload.